A Bleak Future Awaits Nurses in Traditional Employment Worldwide: Insights on Practice and Career Alternatives - Tracey McDonald (Pacific Rim International Journal of Nursing Research, 2023)
The COVID-19 pandemic has tested world leaders’ capacity to manage, and they have been found wanting. Traditional, institutionalised health services will shortly be unsustainable due to unconvincing leadership and inept managerial capacity to identify and alleviate risks to nurses and other workers on the pandemic front line. The aim of this paper is to share insights on nursing career and practice options to provide nursing services to our communities; and canvass anticipated resistance to nurses choosing autonomous practice models in independent business approaches to health care provision. From analysis of the evidence and literature, it was found that the systematic ill treatment and mismanagement of nurses during the COVID-19 pandemic is appalling. Nurses are exiting hospitals and health systems across the globe. Some are leaving nursing itself. On any measure, the situation is a wholesale disaster and a wanton waste of skilled and dedicated people. When hospital and health systems become too toxic for nurses and nursing services to function fully and thrive, and when government officials and politicians trivialise and disrespect the work and value of nursing, it is time for nurses to consider other employment and practice model options. In conclusion, A groundswell of support is needed for nurses to remove normalised policies that bind them to medical control, and to break medical monopoly on universal health insurance funding to permit access by nurses to sufficient specified items to earn a wage as independent practitioners. The implications for nursing and health policy makers are: nurse safety and practice integrity need to be central to policy deliberations that affect spending on risk management and reduction. Policies that put nurses and patients at increased risk encourage those with a choice, to abandon unsafe health system employment. Administrative accountability for staff and patient safety affected by their decisions has long been neglected in health systems around the world. It is time for a reckoning.